2003
DOI: 10.1097/00001703-200308000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The prognostic value of salpingoscopy during operative laparoscopy for tubal factor infertility in terms of reproductive outcome has been confirmed. The prognostic significance of microsalpingoscopy needs further validation in large-scale clinical trials. Transvaginal hydrolaparoscopy and fertiloscopy appear to be an alternative to hysterosalpingography as a first line procedure to investigate female infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…The ability of salpingoscopy or falloposcopy to provide better patient selection should be further evaluated in case of fimbrial pathologies [7,8].…”
Section: Patent Phimosismentioning
confidence: 99%
“…The ability of salpingoscopy or falloposcopy to provide better patient selection should be further evaluated in case of fimbrial pathologies [7,8].…”
Section: Patent Phimosismentioning
confidence: 99%
“…[28][29][30] Thus, while laparascopic adhesiolysis can restore external tubal anatomy to facilitate oocyte pickup, tubal function may still be compromised if the endosalpinx is damaged. 31 This was clearly demonstrated in a study of 51 patients with periadnexal adhesions or hydrosalpinx, who underwent adhesiolysis or salpingostomy, respectively, in addition to salpingoscopy. 28 Patients with normal tubal mucosa at the time of laparoscopic surgery had 71% and 64% cumulative pregnancy rates in the adhesiolysis and salpingostomy groups, respectively, while those with intraluminal tubal damage had no intrauterine pregnancies.…”
Section: B) Salpingoscopymentioning
confidence: 90%
“…There is evidence in the published literature that suggests that pelvic adhesion can cause infertility 3,[105][106][107] with an increased risk of ectopic pregnancy, 4 should the patient conceive. In fact, it has been shown that adhesions may contribute to infertility in about 40% of infertile couples 100 and represent the sole infertility factor in up to 15% of cases.…”
Section: Adhesion-associated Infertility Following Previous CD Versusmentioning
confidence: 99%